Hume subject in paradigm of ecoloqical thinging - Najder-Stefaniak, Krysytna (Studia Ecologiae et Bioethicae, 2004)
The paper presents the notion of human subjects. The author emphasizes the fact, that the thinking in ecological paradigm demand of own notion of the subject so as to substantiate the notion of responsibility and creative possibility of man. Autor state that in thinking the metaphor of an ecosystem is indispensable the notion of subjectivity fits in with the nation of man.